Urbanization drives genetic differentiation in physiology and structures the evolution of pace-of-life syndromes in the water flea Daphnia magna. Issue 1883 (18th July 2018) - Brans, Kristien I.; Stoks, Robby; De Meester, Luc
Abstract : Natural and human-induced stressors elicit changes in energy metabolism and stress physiology in populations of a wide array of species. Cities are stressful environments that may lead to differential selection on stress-coping mechanisms. Given that city ponds are exposed to the urban heat island effect and receive polluted run-off, organisms inhabiting these ecosystems might show genetic differentiation for physiological traits enabling them to better cope with higher overall stress levels. A common garden study with 62 Daphnia magna genotypes from replicated urban and rural populations revealed that urban Daphnia have significantly higher concentrations of total body fat, proteins and sugars. Baseline activity levels of the antioxidant defence enzymes superoxide dismutase (SOD) and glutathione-S-transferase (GST) were higher in rural compared with city populations, yet urban animals were equally well protected against lipid peroxidation. Our results add to the recent evidence of urbanization-driven changes in stress physiology and energy metabolism in terrestrial organisms. Combining our results with data on urban life history evolution in Daphnia revealed that urban genotypes show a structured pace-of-life syndrome involving both life-history and physiological traits, whereas this is absent in rural populations.